National Analysis of Risk Factors for Nasal Fractures and Associated Injuries in Trauma - Pham, Tiffany T. (Craniomaxillofac Trauma Reconstr, 2019)
Nasal fractures account for up to 58% of facial fractures. However, the literature characterizing associated injuries and risk factors for nasal fractures is sparse and is mostly composed of single-center experiences. This study sought to provide a large descriptive analysis and identify associated injuries and risk factors for nasal fractures in trauma using a national database. A retrospective analysis of the National Trauma Data Bank (NTDB) from 2007 to 2015 was performed. Patients ≥18 years of age with nasal fractures were included. A multivariable logistic regression model was used to identify predictors for nasal fracture in trauma. Of 5,494,609 trauma patients in the NTDB, 255,533 (4.6%) had a nasal fracture. Most were male (74.8%) with a mean age of 45.6 years. Blunt trauma accounted for 90.5% of fractures, with motor vehicle accident being the most common mechanism (27.5%). Closed fractures occurred in 93.0% of patients. Concomitant injuries included traumatic brain injury (TBI; 56.9%), malar/maxillary fracture (27.9%), and open wound of the face (38.6%) and nose (9.5%). Of all patients, 10.1% underwent closed or open reductions at index hospitalization. The strongest associated injuries with nasal fracture included open wound of the nose (odds ratio [OR]: 8.71, 95% confidence interval [CI]: 8.49–8.94, p  < 0.001), epistaxis (OR: 5.26, 95% CI: 4.59–6.02, p  < 0.001), malar/maxillary fracture (OR: 4.38, 95% CI: 4.30–4.45, p  < 0.001), and orbital fracture (OR: 3.99, 95% CI: 3.91–4.06, p  < 0.001). Nasal fractures are common traumatic injuries with more than 90% occurring by blunt mechanism and over half suffering from a concomitant TBI. The strongest associated injury with nasal fracture is an open wound of the nose.